Propylene glycol supplementation response in multiovulated cows for embryo production - Molina-Coto, Roger Eduardo (2018)
Multiovulation and embryo transfer is a technique used in genetic breeding programs. The synchronization-multi ovulation protocols of bovine embryo donors, as well as the embryo collection technique, have improved, however, the technique should still be maximized. This study was done with the objective of evaluating the effect of the administration of propylene glycol (PPG) in multiovulated donor cows on the production and quality of embryos. The study was conducted in Pococi, Limon, Costa Rica, from February 2011 to January 2012. Daily and oral administration of 300 mg PPG was given from one week prior to one week after the starting of the synchronization-multiovulation protocol. Embryo flushing was performed every two months and seven cows were used. Ovarian evaluations were performed using transrectal ultrasonography before and during the days of the synchronization-multiovulation treatment. The embryos were collected and classified at the age of seven days. Treatment with PPG did not affect the number and size of ovarian follicles as measured by ultrasonography. Likewise, the number of structures collected and their quality did not improve with supplementation. The results of the experiment suggest that other factors, unrelated to the effect of PPG supplementation, affect the animal response to treatments for multiovulation and embryo collection.